Sosialisasi Pembatasan Sosial berskala Besar Via zoom dalam Manajemen Bencana Pandemi Covid 19 di Kota Bengkulu - Putri, Sudriyanti; Efendi, Rustam; Pajri, Nirwan; Widayanti, Elis; Rahmawati, Yuni (Jurnal Kewirausahaan dan Bisnis, 2021)
Bengkulu, which has the motto "Sekundang setungguan seio sekata", is a province with a population of 2,001,578 people, the majority of whom are farmers, planters, laborers and traders. Bengkulu residents are accustomed to living in mutual cooperation as a characteristic of Indonesian society. When the COVID-19 outbreak entered Bengkulu, their spirit of togetherness was immediately summoned. Starting from the Governor to the people in the most remote areas, they obeyed and implemented health protocols. The various limitations they have do not necessarily make them give up. Instead, these limitations became a whip for the people of Bengkulu to continue to suppress the spread of COVID-19. With hard work, Bengkulu has achieved a cure rate of more than 70%. The key to all COVID-19 treatments in Bengkulu is cooperation, communication, and hard work.